Changes in glucose-induced plasma active glucagon-like peptide-1 levels by co-administration of sodium-glucose cotransporter inhibitors with dipeptidyl peptidase-4 inhibitors in rodents - Takahiro Oguma; Chiaki Kuriyama; Keiko Nakayama; Yasuaki Matsushita; Kumiko Hikida; Minoru Tsuda-Tsukimoto; Akira Saito; Kenji Arakawa; Kiichiro Ueta; Masabumi Minami; Masaharu Shiotani (Elsevier, 2016)
We investigated whether structurally different sodium-glucose cotransporter (SGLT) 2 inhibitors, when co-administered with dipeptidyl peptidase-4 (DPP4) inhibitors, could enhance glucagon-like peptide-1 (GLP-1) secretion during oral glucose tolerance tests (OGTTs) in rodents. Three different SGLT inhibitors-1-(β-d-Glucopyranosyl)-4-chloro-3-[5-(6-fluoro-2-pyridyl)-2-thienylmethyl]benzene (GTB), TA-1887, and canagliflozin-were examined to assess the effect of chemical structure. Oral treatment with GTB plus a DPP4 inhibitor enhanced glucose-induced plasma active GLP-1 (aGLP-1) elevation and suppressed glucose excursions in both normal and diabetic rodents. In DPP4-deficient rats, GTB enhanced glucose-induced aGLP-1 elevation without affecting the basal level, whereas metformin, previously reported to enhance GLP-1 secretion, increased both the basal level and glucose-induced elevation. Oral treatment with canagliflozin and TA-1887 also enhanced glucose-induced aGLP-1 elevation when co-administered with either teneligliptin or sitagliptin. These data suggest that structurally different SGLT2 inhibitors enhance plasma aGLP-1 elevation and suppress glucose excursions during OGTT when co-administered with DPP4 inhibitors, regardless of the difference in chemical structure. Combination treatment with DPP4 inhibitors and SGLT2 inhibitors having moderate SGLT1 inhibitory activity may be a promising therapeutic option for improving glycemic control in patients with type 2 diabetes mellitus.